The Personal Becomes the Political: Womanist Resilience and Butlerian Agency in Possessing the Secret of Joy - Meymanat Daneshvari; Bakhtiar Sadjadi (Critical Literary Studies)
The present paper explores Alice Walker’s Possessing the Secret of Joy in an attempt to highlight the importance of the establishment of a well-defined identity as the crucial step in the life of Tashi, a victim of genital mutilation. She becomes whole and healthy once she finds a voice and remakes her severed ties with the black community. Her individual acts of rebellion are complemented with collective political action against genital mutilation. Butler’s view, agency is a restorative energy which works against fragmentation and opens a new possibility for psychic healing as the essential path to the formation of an individual identity. The paper explores the path taken by the novel’s female protagonist to validate her right as an active agent and defy the objectifying assumptions which deprive women of the right to be treated as human subjects. The long-held womanist aspirations shared by Tashi and her fellow sufferers matched by the desire to restore the lost agency is the only hope given to black women to establish their own voice. The protagonist’s final healing is thus achieved through the healthy interaction between individual as well as collective acts of rebellion: individual agency accompanied by political and social transformation.